Decolonizing Feminism: From Reproductive Abuse to Reproductive Justice - Stote, Karen (Atlantis, 2017)
This paper asks why reproductive gains have sometimes amounted to reproductive abuse for Indigenous women in Canada. Guided by an intersectional and decolonial approach, it provides a historical material critique of the individualized rights discourse and reformist goals that tend to underlay feminist struggles in Canada. It explores how western feminism might support decolonization and reproductive justice.